1997
DOI: 10.1038/sj.bmt.1701022
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of selective renal shielding in patients undergoing total body irradiation in preparation for bone marrow transplantation

Abstract: Summary:own is late or long-term renal toxicity. [2][3][4][5][6][7][8][9][10][11] The renal toxicity described consists of a group of clinical signs including hypertension, anemia, and decreased glomerular filThe purpose of this study was to evaluate the effect of partial renal shielding used in conjunction with total tration rate (GFR) with occasional proteinuria and microscopic hematuria, and edema. Biopsies of the affected body irradiation (TBI) on the incidence of bone marrow transplantation nephropathy (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
3
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 8 publications
4
68
3
1
Order By: Relevance
“…Our study has also confirmed the previous observation described by Lawton et al 12 that shielding the kidneys during TBI reduces renal injury. At the end of the 3-year follow-up period, the shielded patients had a CrCl that was 62% higher than those who did not.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study has also confirmed the previous observation described by Lawton et al 12 that shielding the kidneys during TBI reduces renal injury. At the end of the 3-year follow-up period, the shielded patients had a CrCl that was 62% higher than those who did not.…”
Section: Discussionsupporting
confidence: 82%
“…Beginning in 1992, the renal shielding was increased to 30% for a resulting renal dose of 9.8 Gy. 12 All patients received GVHD prophylaxis consisting of T cell depletion of the donor marrow and cyclosporine as described previously. 13 There is approximately a 1.7 Ϯ 0.4 log 10 depletion of functional T lymphocytes from the donor marrow.…”
Section: Conditioning Regimenmentioning
confidence: 99%
“…Chemo-irradiation conditioning was done as described in Lawton et al (8). The standard TBI dose was 14 Gy, in nine equal fractions over three days, using a dose rate of 8 to 20 cGy/minute and with at least four hours between fractions.…”
Section: Treatment Planmentioning
confidence: 99%
“…BMT nephropathy in its most severe form appears similar to hemolytic uremic syndrome (HUS), which has also been linked to TBI used for the conditioning regimen (7). Finally, partial kidney shielding at the time of TBI has reduced the occurrence rates of BMT nephropathy (8).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Although exposure of kidneys to radiation during hematopoietic cell transplantation has been hypothesized as a risk factor for bone marrow transplant nephropathy, studies have shown conflicting data regarding renal shielding and long-term renal insufficiency. 5,[8][9][10][11][12] Other causes of thrombotic microangiopathy must be considered in hematopoietic cell transplant recipients, including exacerbation of endothelial injury by chemotherapy, immune-mediated injury, and perhaps most notably, cyclosporine inhibitor toxicity, given as prophylaxis or treatment for graft-versus-host disease.…”
mentioning
confidence: 99%